Research on simple query algorithm during mobile terminal disconnection - Ru-bing LIANG; Qiong LIU (Tongxin xuebao)
A simple query processing algorithm SQPID (simple query processing in disconnection),was proposed.Main idea of SQPID is to build integrated related semantic cache item about current query through combining and clipping operations.In order to simplify the procedure,SQPID's combine does not involve indirect relativity estimation.The results of simulated experiments show that SQPID's query response time and degree of accuracy better meet client's requirements than QPID algorithm.